Effects of a Food Supplement Containing Hydrolyzed Collagen on Pain Perception, Joint Range, and Quality of Life in People with Chronic Knee Pain - Juan Carlos Salinas-Camargo; Cristian Marín-Pagán; Rosario Victoria Álvarez-Gil; Francisco Javier Martínez-Noguera; María Cabrera-Cabrera; Josep Manuel Llabrés-Laguarda; María Isabel Vasallo-Morillas; Pedro E. Alcaraz (Diseases)
Background: Joint pain can impair joint function and limit a person’s ability to perform basic tasks and quality of life. The most used treatment is the pharmacological one. An alternative is the use of collagen-based food supplements. However, it remains a challenge to continue to develop new formulations to improve their efficacy. Objectives: The aim was to evaluate the long-term effectiveness of a food supplement based on hydrolyzed collagen alongside other active ingredients on knee joint pain, range of motion, and quality of life questionnaires in a moderately active population. Methods: A randomized, double-blind, and controlled study with two arms was completed with 80 participants, who took the prescribed supplementation (Curarti® Selectium) or placebo for 40 days. Results: The supplement group showed a reduction of pain felt just after waking up in the morning. A statistically significant reduction in felt pain 3 h after exercise was observed at week 6 for the new product formula group compared to the placebo group. The symptoms associated with knee problems (KOOS) showed significant differences between groups. In functional capacity (WOMAC), it was found that the improvement was greater in the group treated with investigational formula (IF) than in the placebo group. The 36-item short form health survey (SF-36) about quality of life showed that the individuals who took IF improved with respect to those who took a placebo. Conclusions: The intake of Curarti® Selectium for 40 days is effective in reducing joint pain at rest and after physical exercise, as well as maintaining the perception of quality of life, while allowing the physical functionality of the joint.